2021
DOI: 10.1101/2021.01.09.21249189
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of Visual Impairment with Brain Structure

Abstract: ObjectiveTo investigate the association of visual impairment (VI) with brain structures in the UK Biobank Study.MethodsThe UK Biobank Study is a large prospective study that recruited more than 500,000 participants aged 40-69 from 2006 to 2010 across the UK. Visual acuity (VA) of worse than 0.3 LogMAR units (Snellen 20/40) was defined as VI. Structural magnetic resonance imaging (MRI) data were obtained using a 3.0-T MRI imager. Volumetric measures of five global brain volumes (total brain volume, total grey m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Third, the reduced information input secondary to sensory impairment could result in reduced stimulation of the cognitive domains of the brain (Griffiths et al, 2020 ). Evidence from recent studies found decreased volumes of specific brain regions involved in visual processing, and atrophy of total brain volume and the limbic system implicated in neurodegenerative diseases in visually impaired individuals (Bathelt et al, 2020 ; Zhu et al, 2021 ). Fourth, sensory impairment could contribute to the development of dementia directly or indirectly mediated by depression, one of the most well-established risk factors for dementia (Jorm, 2000 ; Cacioppo and Hawkley, 2009 ; Steenland et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Third, the reduced information input secondary to sensory impairment could result in reduced stimulation of the cognitive domains of the brain (Griffiths et al, 2020 ). Evidence from recent studies found decreased volumes of specific brain regions involved in visual processing, and atrophy of total brain volume and the limbic system implicated in neurodegenerative diseases in visually impaired individuals (Bathelt et al, 2020 ; Zhu et al, 2021 ). Fourth, sensory impairment could contribute to the development of dementia directly or indirectly mediated by depression, one of the most well-established risk factors for dementia (Jorm, 2000 ; Cacioppo and Hawkley, 2009 ; Steenland et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%